Empowerment And Preservation of Mekotek Dance in the Tourist Area of Munggu Village, Mengwi District, Badung Regency - Desak Gde Dwi Arini; Putu Ayu Sriasih Wesna; Ni Ketut Sukiani (Fakultas Hukum, Universitas Warmadewa, 2022)
Mekotek dance is fragmentary of the mekotek tradition in Munggu Tourism Village which includes intellectual works within the scope of copyright and has been stated in real form and has rights that need legal protection. The aims of this study is to analyze the implementation of copyright registration for mekotek dance and to find out the form of legal protection. The methods of implementation carried out in the community service program are by Business Law Program, Sastra Faculty Program, and The partnership of Munggu Village tourist area Mengwi district Badung Regency. The results obtained in the study as follows, the implementation of copyright registration for dance mekotek can be done online and offline. For the management of the registration process, it is represented by the Chairman of the Munggu Village Tourism Awareness Group, namely Mr. Putu Suada. Of course, the implementation starts from looking for requirements documents such as the identity of the parties, filling out the application letter; affidavit of ownership; transfer letter of rights where all must be pdf, and proof of the work of mekotek dance in the form of storylines and MP3 videos. The registered creation will be subject to the registration fee. After everything is collected and then sent to the HAKI Partner to take care of online by waiting approximately 1 month to get the results in the form of copyright certificates. Therefore, the results of the registration will be in line to obtain legal protection and lead to quality tourism.